Genetic differentiation without mimicry shift in a pair of hybridizing Heliconius species (Lepidoptera: Nymphalidae). (3rd May 2013) - Mérot, Claire; Mavárez, Jesús; Evin, Allowen; Dasmahapatra, Kanchon K.; Mallet, James; Lamas, Gerardo; Joron, Mathieu
Abstract : Butterflies in the genus Heliconius have undergone rapid adaptive radiation for warning patterns and mimicry, and are excellent models to study the mechanisms underlying diversification. In Heliconius, mimicry rings typically involve distantly related species, whereas closely related species often join different mimicry rings. Genetic and behavioural studies have n how reproductive isolation in many pairs of Heliconius taxa is largely mediated by natural and sexual selection on wing colour patterns. However, recent studies have uncovered new cases in which pairs of closely related species are near‐perfect mimics of each other. Here, we provide morphometric and genetic evidence for the coexistence of two closely related, hybridizing co‐mimetic species on the eastern slopes of the Andes, H. melpomene amaryllis and H. timareta ssp. nov., which is described here as H. timareta thelxinoe . A joint analysis of multilocus genotyping and geometric morphometrics of wing shape shows a high level of differentiation between the two species, with only limited gene flow and mixing. Some degree of genetic mixing can be detected, but putative hybrids were rare, only one of 175 specimens being a clear hybrid. In contrast, we found phenotypic differentiation between populations of H. timareta thelxinoe, possibly indicative of strong selection for local mimicry in different communities. In this pair of species, the absence of breakdown of genetic isolation despite near‐identical wing patterns implies that factors other than wing patterns keep the two taxa apart, such as chemical or behavioural signals, or ecological adaptation along a strong altitudinal gradient. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 830–847.